2013
DOI: 10.3109/13645706.2013.854808
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of laparoscopy in abdominal surgery: A meta-analysis of the effect on infectious outcomes

Abstract: Laparoscopic surgery significantly decreases the risk of superficial SSI but does not affect the risk of organ/space SSI. Experience with technique improves outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…This finding was described in previous research work where scope use significantly reduced SSI rates. 7 , 27 , 28 A review of the literature showed scarce research evidence on SSIs following SB surgeries; most researchers had studied SSIs of either the large bowel alone or in combination with SB surgeries. 10 , 29 , 30 The present study showed that the incidence of SSIs following SB surgery was 10.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was described in previous research work where scope use significantly reduced SSI rates. 7 , 27 , 28 A review of the literature showed scarce research evidence on SSIs following SB surgeries; most researchers had studied SSIs of either the large bowel alone or in combination with SB surgeries. 10 , 29 , 30 The present study showed that the incidence of SSIs following SB surgery was 10.8%.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was concordant with results from other research. 28 A possible explanation for the higher incidence of SSIs in emergency surgeries could be attributed to inadequate preoperative preparation, as these surgeries usually take place beyond normal clinical working hours. Therefore, it is of high importance to emphasize the management of emergency surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1 , the incidence of SSI in emergency surgery cases was higher than in elective surgery cases (8.4% versus 2.5%, respectively), which is in accordance with other studies. 21 , 22 Patients with acute abdominal pain account for the majority of emergency surgeries, and are at high perioperative risk for SSI because of the infected operation, especially at the preoperative infection lesions. On the other hand, most of the emergency surgeries were carried out beyond normal duty working hours and inadequate preoperative preparation might be a possible explanation for the higher incidence of SSI.…”
Section: Discussionmentioning
confidence: 99%
“…La visión de cirugía sin estrés y sin dolor podría convertirse en realidad con mayor investigación de esta prometedora estrategia. Cabe destacar que algunos elementos del fast-track son usados de rutina y aisladamente por algunos cirujanos, sin la aplicación de todo el protocolo (por ejemplo, retiro temprano de sondas o drenajes, o ayunos cortos y dieta temprana) 32,33 . Sin embargo, es la implementación simultánea de todas las herramientas de la estrategia, las que pueden acelerar la recuperación posquirúrgica.…”
Section: Diferencia De Medias Sopesadas Entre Cuidado Convencional (C...unclassified